IMMU-26. DISEASE CONTROL IN A PEDIATRIC PATIENT WITH NEWLY DIAGNOSED GLIOBLASTOMA MULTIFORME (GBM) AND SOMATIC HIGH MICROSATELLITE INSTABILITY (MSI-H) WITH PD-1 INHIBITOR NIVOLUMAB (NIVO) ONLY AND NO FOCAL RADIOTHERAPY (RT). (4th December 2020) - Larkin, Trisha; Blatt, Jason; Gururangan, Sridharan
Abstract: Immune checkpoint inhibitors that target programmed death receptor-1 (PD-1) have recently been shown to be a promising option for the management of recurrent mismatch repair (MMR) deficient GBM following radiotherapy. We report a case of a 9-year-old boy who presented with a 6 week history of frontal headaches and was found to have a left frontal lobe mass. Pathology obtained from a gross total resection (GTR) was consistent with classic GBM, WHO Grade IV. Neuroimaging four weeks following initial resection was remarkable for local recurrence. The patient underwent another GTR of the tumor at our center. While pathology again confirmed GBM, GlioSequencing of tumor tissue from second resection showed MSI-H, NF2 mutation p.R338H, NF1 mutations p.R2450* and pI193Yfs*11, TP53 mutations p.R213* and p.R273C, EGFR mutation, and multiple variants of uncertain significance. Germline testing was negative for MMR deficiency or other deleterious mutations. Parents opted to defer radiotherapy and consented to monotherapy treatment with Nivolumab (Opdivo, BMS pharmaceuticals, USA), a PD-1 inhibitor, at a dose of 3 mg/kg administered every two weeks. Our patient is now 22 months post-second resection and continues to receive Nivolumab without evidence of recurrent disease or adverse autoimmune effects from PD-1 blockade. He has remained in school with good academic performance and has exhibited no regression of functional status during the entirety of his treatment course. This case provides evidence of possible efficacy of PD-1 blockade without focal radiotherapy in this child with GBM and somatic MSI instability.